Алгебра 8 класс Ю.Н.Макарычев, Н.Г.Миндюк, К.И.Нешков, С.Б.Суворова

Алгебра 8 класс Ю.Н.Макарычев, Н.Г.Миндюк, К.И.Нешков, С.Б.Суворова

авторы: , , , .
издательство: "Просвещение" 2013 г

Раздел:

Номер №57

Упростите выражение:
а)
$\frac{16}{x - 4} - \frac{x^2}{x - 4}$
;
б)
$\frac{25}{a + 5} - \frac{a^2}{a + 5}$
;
в)
$\frac{3a - 1}{a^2 - b^2} - \frac{3b - 1}{a^2 - b^2}$
;
г)
$\frac{x - 3}{x^2 - 64} + \frac{11}{x^2 - 64}$
;
д)
$\frac{2a + b}{(a - b)^2} + \frac{2b - 5a}{(a - b)^2}$
;
е)
$\frac{13x + 6y}{(x + y)^2} - \frac{11x + 4y}{(x + y)^2}$
.

Решение а

$\frac{16}{x - 4} - \frac{x^2}{x - 4} = \frac{16 - x^2}{x - 4} = \frac{(4 - x)(4 + x)}{x - 4} = \frac{(4 - x)(4 + x)}{-(4 - x)} = -(4 + x) = -4 - x$

Решение б

$\frac{25}{a + 5} - \frac{a^2}{a + 5} = \frac{25 - a^2}{a + 5} = \frac{(5 - a)(5 + a)}{5 + a} = 5 - a$

Решение в

$\frac{3a - 1}{a^2 - b^2} - \frac{3b - 1}{a^2 - b^2} = \frac{3a - 1 - 3b + 1}{a^2 - b^2} = \frac{3a - 3b}{a^2 - b^2} = \frac{3(a - b)}{(a - b)(a + b)} = \frac{3}{a + b}$

Решение г

$\frac{x - 3}{x^2 - 64} + \frac{11}{x^2 - 64} = \frac{x - 3 + 11}{x^2 - 64} = \frac{x + 8}{(x - 8)(x + 8)} = \frac{1}{x - 8}$

Решение д

$\frac{2a + b}{(a - b)^2} + \frac{2b - 5a}{(a - b)^2} = \frac{2a + b + 2b - 5a}{(a - b)^2} = \frac{3b - 3a}{(a - b)^2} = \frac{3(b - a)}{(a - b)^2} = \frac{-3(a - b)}{(a - b)^2} = -\frac{3}{a - b} = \frac{3}{b - a}$

Решение е

$\frac{13x + 6y}{(x + y)^2} - \frac{11x + 4y}{(x + y)^2} = \frac{13x + 6y - 11x - 4y}{(x + y)^2} = \frac{2x + 2y}{(x + y)^2} = \frac{2(x + y)}{(x + y)^2} = \frac{2}{x + y}$